APPLICATION OF RECURRENT NETWORKS TO REASONING - Iza Mikeleiz, Mauricio (Anales de Psicología / Annals of Psychology, 2003)
The logical ordering of events facilitates the processing of narratives. If readers are going to perform an inference in order to make easier their assimilation of an upcoming text, it seems likely that they will perform an inference closely related to the causal coherence of the narrative. Therefore, an appropriate approach to this issue should determine the contexts in which readers perform elaborative inferences. In this paper, we will show that a recurrent net can be able to reasoning and interact with a contextual module.